Antibiotic stewardship in perinatal and neonatal care. Issue 5 (October 2017) - Ramasethu, Jayashree; Kawakita, Tetsuya
Abstract: The spread of antibiotic resistance due to the use and misuse of antibiotics around the world is now a major health crisis. Neonates are exposed to antibiotics both before and after birth, often empirically because of risk factors for infection, or for non-specific signs which may or may not indicate sepsis. There is increasing evidence that, apart from antibiotic resistance, the use of antibiotics in pregnancy and in the neonatal period alters the microbiome in the fetus and neonate with an increased risk of immediate and long-term adverse effects. Antibiotic stewardship is a co-ordinated program that promotes the appropriate use of antibiotics, improves patient outcomes, reduces microbial resistance, and decreases the spread of infections caused by multidrug-resistant organisms. This review addresses some of the controversies in antibiotic use in the perinatal period, examines opportunities for reduction of unnecessary antibiotic exposure in neonates, and provides a framework for antibiotic stewardship in neonatal care.